Daily Consumption of Virgin Coconut Oil Increases High-Density Lipoprotein Cholesterol Levels in Healthy Volunteers: A Randomized Crossover Trial - Surarong Chinwong (2018)
© 2017 Surarong Chinwong et al. This open-label, randomized, controlled, crossover trial assessed the effect of daily virgin coconut oil (VCO) consumption on plasma lipoproteins levels and adverse events. The study population was 35 healthy Thai volunteers, aged 18-25. At entry, participants were randomly allocated to receive either (i) 15 mL VCO or (ii) 15 mL 2% carboxymethylcellulose (CMC) solution (as control), twice daily, for 8 weeks. After 8 weeks, participants had an 8-week washout period and then crossed over to take the alternative regimen for 8 weeks. Plasma lipoproteins levels were measured in participants at baseline, week-8, week-16, and week-24 follow-up visits. Results. Of 32 volunteers with complete follow-up (16 males and 16 females), daily VCO intake significantly increased high-density lipoprotein cholesterol by 5.72 mg/dL (p = 0.001) compared to the control regimen. However, there was no difference in the change in total cholesterol, low-density lipoprotein cholesterol, and triglyceride levels between the two regimens. Mild diarrhea was reported by some volunteers when taking VCO, but no serious adverse events were reported. Conclusion. Daily consumption of 30 mL VCO in young healthy adults significantly increased high-density lipoprotein cholesterol. No major safety issues of taking VCO daily for 8 weeks were reported.